REPRESENTATION OF EXISTENTIALIST FEMINISM IN “SUFFRAGETTE” MOVIE SCRIPT - Yuhendra Yuhendra; Nofrika Sari; Rika Andriani; Afdaleni Afdaleni; Albert Albert; Haris Syukri; Dewi Ade Putri (LLDIKTI Wilayah X, 2026)
This research examines the representation of existentialist feminism in Abi Morgan’s script for the film Suffragette. While previous studies on the film primarily discuss historical or broad socio-political paradigms, this research highlights its novelty by exploring how female characters actively subvert their status as